Accounting abuse - Bartoňová, Tereza; Roubíčková, Jaroslava, 1954-; Müllerová, Libuše, 1945-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
The thesis "Abuse accounting" have focused on the basic definitions of the creative accounting and deception, categorizing and methods of implementation. The following chapters are directed to the field of economic crime, the most common description of the perpetrators of this illegal activity and comparing forensic investigation and auditing.In conclusion, the thesis is plunging attention to practical examples of abuse accounts both worldwide and in the Czech Republic.
Vedoucí práce: Jaroslava Roubíčková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor dipl. práce]; diplomové práce; master's theses